Ensuring sustainable development through groundwater management, area one, south western desert, Egypt - Gamal H. El Saeed; Neveen B. Abdelmageed; Peter Riad; M Komy (Institute of Advanced Engineering and Science, 2020)
Darb El-Arbeain area lies between long. 29o 00/ and 31o 00/ E and lat. 22o 00/ and 24o 30/ N. It is divided into three separate areas; The northern part extends 90 km to the south from Paris town and has an area of 90 km2. In this study four suggested scenarios of pumping rates have been explored to fit with the Egyptian ministry of irrigation using the three dimensional finite difference flow model (MODFLOW) to simulate the flow system. These scenarios include: first, model will run with abstraction from the aquifers equal 110 %, 180%, 280%, and 370% of calculated initial recharge. Results indicate that the second scenario has the most economic scenario on the area. The fourth scenario caused the highest increase of drawdown values which should be avoided.